Altered Static and Dynamic Spontaneous Neural Activity in Drug-Naïve and Drug-Receiving Benign Childhood Epilepsy With Centrotemporal Spikes - Jiang, Sisi; Luo, Cheng; Huang, Yang; Li, Zhiliang; Chen, Yan; Li, Xiangkui; Pei, Haonan; Wang, Pingfu; Wang, Xiaoming; Yao, Dezhong (Frontiers in Human Neuroscience, 2020)
The present study aims to investigate intrinsic abnormalities of the brain and the effect of antiepileptic treatment on brain activity in Benign childhood epilepsy with centrotemporal spikes (BECTS). Twenty-six drug-naïve patients(DNP) and 22 drug-receiving patients (DRP) with BECTS were collected in this study. The static amplitude of low-frequency fluctuation (sALFF) and dynamic ALFF(dALFF) was applied to resting-state fMRI data. Functional connectivity (FC) analysis was further performed for affected regions identified by static and dynamic analysis. One-way analysis of variance and post-hoc statistical analyses were performed for between-group differences. Abnormal sALFF and dALFF values were correlated with the clinical features of patients. Compared with healthy controls (HC), the DNP group demonstrated alterations of sALFF and/or dALFF in the medial prefrontal cortex(MPFC), supplementary motor areas(SMA), cerebellum, hippocampus, pallidum, and cingulate cortex, in which the values were close to normal in DRP. Notably, sALFF and dALFF showed specific sensitivity in detecting abnormalities in basal ganglia and cerebellum. Additionally, DRP showed additional changes in the precuneus, inferior temporal gyrus, superior frontal gyrus, and occipital visual cortex. Compared with HC, the DNP showed increased FC in default network and motion-related networks, and the DRP showed decreased FC in the default network. The MPFC, hippocampus, SMA, basal ganglia, and cerebellum are indicated to be intrinsically affected regions and effective therapeutic targets. And the FC profiles of default and motion-related networks might be potential core indicators for clinical treatment. This study revealed potential neuromodulatory targets and helped understand the pathomechanism of BECTS. Static and dynamic analyses should be combined to investigate neuropsychiatric disorders.